Aggressive epidermotropic cutaneous CD8+ lymphoma: a cutaneous lymphoma with distinct clinical and pathological features. Report of an EORTC Cutaneous Lymphoma Task Force Workshop. Issue 4 (24th February 2015) - Robson, Alistair; Assaf, Chalid; Bagot, Martine; Burg, Gunter; Calonje, Eduardo; Castillo, Christine; Cerroni, Lorenzo; Chimenti, Nicola; Dechelotte, Pierre; Franck, Frederic; Geerts, Maria; Gellrich, Sylke; et al.
Abstract : Aims: Aggressive epidermotropic cutaneous CD8 + lymphoma is currently afforded provisional status in the WHO classification of lymphomas. An EORTC Workshop was convened to describe in detail the features of this putative neoplasm and evaluate its nosological status with respect to other cutaneous CD8 + lymphomas. Methods and results: Sixty‐one CD8 + cases were analysed at the workshop; clinical details, often with photographs, histological sections, immunohistochemical results, treatment and patient outcome were discussed and recorded. Eighteen cases had distinct features and conformed to the diagnosis of aggressive epidermotropic cutaneous CD8 + lymphoma. The patients typically present with widespread plaques and tumours, often ulcerated and haemorrhagic, and histologically have striking pagetoid epidermotrophism. A CD8 + /CD45RA + /CD45RO − /CD2 − /CD5 − /CD56 − phenotype, with one or more cytotoxic markers, was found in seven of 18 patients, with a very similar phenotype in the remainder. The tumours seldom involve lymph nodes, but mucosal and central nervous system involvement are not uncommon. The prognosis is poor, with a median survival of 12 months. Examples of CD8 + mycosis fungoides, lymphomatoid papulosis and Woringer–Kolopp disease presented the typical features well documented in the CD4 + forms of those diseases. Conclusions: Aggressive epidermotropic cutaneous CD8 + lymphoma is a distinct lymphoma that warrants inclusion as a distinct entity in future revisions of lymphoma classifications.